Effect of Local Urokinase on Arterial Occlusion of Lower Limbs - Fiessinger, J-N; Aiach, M; Capron, L; Devanlay, M; Vayssairat, M; Juillet, Y (Thrombosis and Haemostasis, 1981)
Sixty nine patients were treated with local intra-arterial urokinase (37,500 U/CTA. hr-1) for recent severe ischemia of lower limbs: 27 (40%) ultimately required amputation. The difference of amputation rate between the groups with and without thrombolysis was not significant (33% v. 42%). A biological study in 6 patients showed that local arterial plasminemia occurred in only 1 patient. Local urokinase does not strongly stimulate “endogenous” thrombolysis and enhances “exogenous” thrombolysis only very inconstantly. A better adaptation of urokinase dosage or the use of an agent with a higher affinity for fibrin might improve the efficiency of local thrombolytic therapy.
Keywords: Thrombolysis; Urokinase; Local urokinase; Lower limbs ischemia